(3JUhQ ebJQM dJWhjQ COGA GdbjGOGJ GdJQHhjI HQjGV GdCWaGd aj VhA eONd GdgjJGLhLj (B:s (3eMGaXI GdbdjhHjI fehPLG (B/s - (3,CejQI YHO GdefYe YHO GdNGdb eMeO s; (3CSGeI eMehO aQGL s; (3QMGH CMeO EHQGgjes (2024)
(3gOa GdHMK JYQa GdEWGQ GdeaGgjej deONd GdgjJGLhLj, hGdcTa Yf GdCSS GdadSajI ddbjGOGJ GdJQHhjI HeQMdI QjGV GdCWaGd, hCgJe GdHMK HEdbGA GdVhA Ydj JWhjQ COGA GdbjGOGJ GdJQHhjI ef NdGd GdfgL GdgjJGLhLj, hGdJYQa Ydj CKQ GdJWhjQ hGdJOQjH GdeSJeQ ddbjGOGJ GdJQHhjI hCKQI Ydj eNQLGJ GdJYde, hbO GSJNOeJ GdHGMKI GdefgL GdhUaj dchfg edGFe dWHjYI GdHMK ef NdGd EYOGO GSJHGfg dLeY GdHjGfGJ, hJchfJ YjfI GdHMK ef GdbjGOGJ GdJQHhjI HeQMdI QjGV GdCWaGd bhGegG (B(54) (3bGFO JQHhj HeMGaXI GdbdjhHjI, hJhUd GdHMK dYOI fJGFL CgegG ofOQI GdHQGeL GdJOQjHjI GddGReI dJWhjQ egGQGJ GdbjGOGJ GdJQHhjI, VYa eYQaI GdbjGOGJ GdJQHhjI HJhXja hJWHjb GdfgL GdgjJGLhLj, UYhHI GSJNOGe GdefUGJ GdJYdjejI GdQbejI, hbO bGeJ GdHGMKI HYed JUhQ ebJQM (B" (3hGbY JWhjQ COGA GdbjGOGJ GdJQHhjI HQjGV GdCWaGd aj VhA eONd GdgjJGLhLj(B"(3, hJhUj HJHfj UGfYj GdbQGQ hGdeNWWjf ddHQGeL GdJOQjHjI hGdGMJjGLGJ GdegfjI ddbjGOGJ GdJQHhjI aj hRGQI GdJQHjI hGdJYdje, hPdc GdYed Ydj JWhjQ GdeYGjjQ GdegfjI hGdJOQjSjI GdNGUI HGdbjGOGJ GdJQHhjI hGdeYdejf aj GdefXheI GdJYdjejI(B. s
The research aims to identify the conceptual framework of the Heutagogical approach, and uncover the philosophical foundations of educational leadership in the kindergarten stage. The research focuses on shedding light on enhancing the performance of educational leaders through the Heutagogical approach, understanding the impact of continuous development and training of educational leaders on learning outcomes. The researcher used a Descriptive approach it is suitable for the nature of the research by preparing a questionnaire to collect data. The research sample consisted of educational leaders in kindergarten in Qalyubia Governorate, with a total of 54 educational leaders. The research reached several conclusions, including the scarcity of necessary training programs to develop the skills of educational leaders, the lack of knowledge among educational leaders in deploying and applying the Heutagogical approach, the difficulty in using digital educational platforms. The researcher proposed a concept "The Reality of Developing the Performance of Educational Leaders in Kindergarten in Light of the Heutagogical Approach", recommending decision-makers and program planners in the Ministry of Education to work on developing professional and academic standards for educational leaders and teachers in the educational system.
(3CWQhMI (B((3eGLSJjQ(B)-(3LGeYI GdbGgQI, (B2024. s
(3HHdjhLQGajG(B: (3UaMGJ (B170-189.s
(3UOQ CjkVG cbQU eOeL(B.s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3QjGV GdGWaGds; (3GdgjJGLhLjs -- (3GdbjGOGJ GdJQHhjIs -- (3QjGV GdCWaGds